PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA APARAT PEMDA: KEPEMIMPINAN, KOMITMEN ORGANISASI, DESENTRALISASI, BUDAYA ORGANISASI SEBAGAI MODERATING - Syafriyanti, Liza; Tanjung, Amries Rusli; Darlis, Edfan (Ensiklopedia Sosial Review, 2019)
The purpose of this study was to examine the effect of budget participation on the performance of local government officials in Riau Province. Additionally it also tested the role of leadership style, organizational commitment, decentralization, and organizational culture as a moderating variable on the relationship between budgetary participation and performance. The research sample was taken with a simple method of proportionate stratified random sampling is the head of department / agency head / head of the bureau, sub head, and the head of the subsections. The population was Echelon III and IV. Data were collected using a questionnaire. Data were analyzed with multiple linear regression method. The results of the data analysis showed that the variables budgetary participation has a positive effect. Meanwhile, the leadership style, decentralization, and organizational culture affect the relationship with the performance of budgetary participation while moderating variable organizational commitment has no effect on the relationship.